EFEKTIVITAS MODEL PEMBELAJARAN SCRAMBLE BERBASIS KONTEKSTUAL TERHADAP KEMAMPUAN BERPIKIR KRITIS IPS SISWA KELAS III SD NEGERI KEBONDALEM 01 BATANG - Farida, Umul; Agustini, Ferina; Wakhyudin, Husni (Jurnal Ilmiah Sekolah Dasar, 2017)
The low level of of third grade learning results on Subjects of social science is encouraging in this research ?. The goal in this research is to know the effectiveness of contextual-based scramble learning model in improving the critical thinking skills of third grade Social Science of Kebondalem 01 Batang Elementary School. This type of research is quantitative. The research method used is one group pretest-posttest design. After the treatment obtained an average grade of 79,833, while for ttest with dk = 23 and Î± = 5% obtained tcount = 10,866 and ttable = 1,714. Because tcount > ttable so Ho rejected Ha accepted. The critical thinking skills of third grade social science reaches the minimum mastery criteria that is 65. In comparative testÂ  the critical thinking skills of Social Science obtained tcount = 13,273 with ttabel = 1,680, so critical thinking skills of Social Sciences after using contextual-based scramble learning model better than before using contextual-based scramble learning model. Based on the calculation of double correlation of the relationship between creative character and cooperation to the critical thinking skills of Social Science of 0,2733. On the significant test of double correlation coefficient with Fcount = 8,469 this price is consulted with Ftabel = 3.47 with Î± = 5% dk numerator = 2 and dk denominator = 21. From the above calculation turns Fcount > Ftabel then there is a correlation between creative character and cooperation to the critical thinking. It can be concluded âthat the contextual-based contextual scramble model effectively improves the critical thinking skills of third-grade Social Science of Kebondalem Elementary School 01 Batangâ.